2020
DOI: 10.1049/iet-map.2019.0849
|View full text |Cite
|
Sign up to set email alerts
|

Planar LTE/sub‐6 GHz 5G MIMO antenna integrated with mmWave 5G beamforming phased array antennas for V2X applications

Abstract: A planar LTE/sub‐6 GHz 5G multiple‐input and multiple‐output (MIMO) antenna integrated with mmWave 5G beamforming phased array antennas for future vehicle‐to‐everything (V2X) applications is proposed. The proposed antenna consists of two multi‐band elements for LTE and sub‐6 GHz 5G bands, two single‐band elements for the sub‐6 GHz 5G band, and four mmWave 5G beamforming phased array antennas. Two compact multi‐band antennas are located on the opposite side of the ground plane and are arranged orthogonally to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…The simulation results in [56] suggested that under such conditions, circular antenna arrays are a better choice compared to other planar array geometries, since circular arrays have a flat gain fluctuation in the main lobe and are thus robust to angle variations. Moreover, the integration of sub-6 GHz and mmWave antenna arrays is becoming a hot topic [57], [58]. It is a promising antenna approach for mmWave-UAV communications and networking as it allows the combination of the advantages of the high and low frequency bands.…”
Section: B Antenna Arraymentioning
confidence: 99%
“…The simulation results in [56] suggested that under such conditions, circular antenna arrays are a better choice compared to other planar array geometries, since circular arrays have a flat gain fluctuation in the main lobe and are thus robust to angle variations. Moreover, the integration of sub-6 GHz and mmWave antenna arrays is becoming a hot topic [57], [58]. It is a promising antenna approach for mmWave-UAV communications and networking as it allows the combination of the advantages of the high and low frequency bands.…”
Section: B Antenna Arraymentioning
confidence: 99%
“…With rapid developments in wireless communication technology, the demands for transparent antennas have increased dramatically in applications [ 1 , 2 ]. Some researchers are studying the results of transparency antenna technology and low resistive thin-film materials [ 3 , 4 , 5 , 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…e majority of the Multiband antennas reported in the literature are all narrowband and with bigger sizes. Many researchers such as [1][2][3][4][5][6][7][8][9][10] have worked in multiband antennas. First, a multiband antenna can be achieved by enabling the higher-order resonant mode of the resonant antenna.…”
Section: Introductionmentioning
confidence: 99%